EVALUASI IMPLEMENTASI PROGRAM JAMINAN KESEHATAN MASYARAKAT (JAMKESMAS) DI KECAMATAN BATURETNO KABUPATEN WONOGIRI - Elisabet Ayu Maharani; Hesti Lestari; Dyah Lituhayu (Journal of Public Policy and Management Review, 2014)
One of the government’s efforts to reduce poverty in Indonesia is giving health aid for poor citizens by giving Jamkesmas (Public Health Assurance) to them. Wonogiri Regency is one of poor regencies in Indonesia, shown by increasing number of people who receive Jamkesmas. There are some aspects that have to be improved in the data collection of Jamkesmas’ beneficiaries in Baturetno District. This is according to the incompleteness of the Jamkesma coverage. Based on this condition, this research is aimed at investigating how Jamkesmas can be enjoyed by poor people listed in Jamkesmas beneficiaries and investigating the achievements of the objectives of Jamkesmas towards poor people in Baturetno District. This research uses the criteria of policy evaluation by William N. Dunn: effectiveness, efficiensy, adequacy, responsiveness, dan accuracy. This research uses qualitative descriptive method. The data were obtained by interview, observation, documentation, and literary review. By using descriptive method, the researcher studied the problem faced by describing the situation of the subjects or the objects of the research based on facts found and based on the real condition. The sources of this research were authorities of Jamkesmas and the beneficieries of Jamkesmas in Baturetno’s Health Center (puskesmas)The results of this reserach were: (1) there is no annual verification or update of the data of Jamkesmas beneficiaries that caused the incompleteness of Jamkesmas beneficiaries, (2) the objectives of Jamkesmas were achieved well in Baturetno District, (3) the acces and quality of health service for poor community were improved, (4) poor neighbourhood had more understanding about the benefits of health service, (5) Jamkesmas program positively affected poorer community in Baturetno Distict, and (6) people felt it hard to complete the requirements of the referral and felt that the registration in the hospitals were convoluted.Based on the above results, it is recommended that the data of Jamkesmas beneficiaries are verified, authorities need to improve coordination so that any information obtained by society is true and complete. The weaknesses of Jamkesmas concluded in this research are expected to improve JKN (National Health Insurance) which is now being implemented by the government.